2021
DOI: 10.3906/bot-2108-30
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, biochemical, and metabolic responses of abiotic plant stress: salinity and drought

Abstract: The most important types of abiotic stress that affect agricultural crops throughout the world, are drought and salinity. These stresses will continue to worsen as the current climate crisis progresses. Plants have evolved a complex set of mechanisms in order to protect themselves from salt and drought. At the macrobiological level, these include alterations in growth rate, water balance, antioxidant defenses, and photosynthesis. Altered metabolites include proline, carbohydrates, glycine betaine, gamma-aminob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 246 publications
(340 reference statements)
2
2
0
Order By: Relevance
“…ese sugars were hallmark biochemical markers in this study, because they play a crucial role in the salt stress response and could be potential target metabolites for salt-tolerant cultivars. Although our analyzed biochemical markers were consistent with many previous studies, each study exhibited characteristic biochemical indicators corresponding to different rice varieties (Arif et al, 2020;Chang et al, 2019;Fu et al, 2018;Goharrizi et al, 2021;W.-S. Wang et al, 2016;Zhao et al, 2014). For example, Goharrizi et al (2021) reported that salt stress significantly altered the accumulation of various carbohydrates, including sucrose, glucose, mannose, galactose, erythrose, sorbose, and xylose.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…ese sugars were hallmark biochemical markers in this study, because they play a crucial role in the salt stress response and could be potential target metabolites for salt-tolerant cultivars. Although our analyzed biochemical markers were consistent with many previous studies, each study exhibited characteristic biochemical indicators corresponding to different rice varieties (Arif et al, 2020;Chang et al, 2019;Fu et al, 2018;Goharrizi et al, 2021;W.-S. Wang et al, 2016;Zhao et al, 2014). For example, Goharrizi et al (2021) reported that salt stress significantly altered the accumulation of various carbohydrates, including sucrose, glucose, mannose, galactose, erythrose, sorbose, and xylose.…”
Section: Discussionsupporting
confidence: 88%
“…Although our analyzed biochemical markers were consistent with many previous studies, each study exhibited characteristic biochemical indicators corresponding to different rice varieties (Arif et al, 2020;Chang et al, 2019;Fu et al, 2018;Goharrizi et al, 2021;W.-S. Wang et al, 2016;Zhao et al, 2014). For example, Goharrizi et al (2021) reported that salt stress significantly altered the accumulation of various carbohydrates, including sucrose, glucose, mannose, galactose, erythrose, sorbose, and xylose. Chang et al (2019) employed GC-MS to determine some sugars in the roots of three rice varieties (Dendang, Fatimawati, and Nipponbare) in response to NaCl stress.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Efficiency and hydraulic safety in species of agricultural interests have been limited to model species like grapevine [30], and less frequently in species like olive [31], but the study of those mechanisms should help to advance the identification of relevant physiological targets in the research of plant material more tolerant of and resilient to dryer conditions [32]. Furthermore, selected traits of water stress tolerance could be candidates for other abiotic stressors that have similar or common response mechanisms, like salinity stress [33,34]. Salinity is widely extensive as a stress factor in agricultural soils interacting with drought stress under a climate change scenario [35,36].…”
Section: Introductionmentioning
confidence: 99%